Edukasi PHBS dan Kecacingan Pada Keluarga Stunting di Kecamatan Pariangan Kabupaten Batusangkar Sumatera Barat - Dewi Yudiana Shinta; Melly Siska Suryani; Muhammad Diki Juliandi; Ikhwan Resmala Sudji; Betti Rosita (CANANG: Jurnal Pengabdian Masyarakat, 2025)
Stunting is a developmental disorder that occurs in children and toddlers. It usually occurs due to chronic malnutrition in the early period of a child's growth. Generally, children who suffer from stunting will look proportional, but when compared to children their age, they will look shorter or stunted. However, not all children who look short or stunted suffer from stunting. A child is said to suffer from stunting if their growth and development is below the standard growth curve according to WHO data. A child who suffers from stunting, growth and development is very poor, not only looks short or stunted, but his intelligence level decreases, speech disorders, and difficulties in learning later, besides that their immune system is lower so that it is easily infected with helminthiasis, viruses and bacteria. Furthermore, helminthiasis infection caused by poor PHBS will cause toddlers and children to suffer from stunting. Therefore, a comprehensive education is carried out about the aspects that cause stunting so that the community understands and understands why their toddlers and children are stunted. This community service was carried out in Pariangan District, Batusangkar Regency, West Sumatra. The results achieved in this educational activity are: definition and characteristics of stunting, impact, PHBS, the onset of helminthiasis and the impact of helminthiasis for toddlers and children and efforts made in preventing stunting itself.